Conventional Karyotyping and Fluorescence In Situ Hybridization: An Effective Strategy for Appropriate Test Utilization. (21st September 2018) - Jebakumar, Deborah; Dobin, Sheila; Rao, Arundhati
Abstract: Introduction: It is common practice to reflexively collect specimens for cytogenetic analysis when the bone marrow aspirate/biopsy samples are collected from the patient. Efficiently managing test utilization in this setting requires both ensuring adequate utilization of needed tests in indicated patients and discouraging nonessential tests in other patients. The aim of our study was to assess the impact of an effective clinician contact-based intervention strategy on cytogenetic orders. Methods: All orders for conventional karyotyping and fluorescence in situ hybridization (FISH) testing on bone marrow specimens from the Hematology-Oncology service with any of the following preliminary diagnoses—"reactive/normal trilineage hematopoiesis/no evidence of leukemia or lymphoma"—at Baylor Scott & White Medical Center from March 2017 to February 2018 were targeted. An email for clarification to the ordering clinician/oncologist was pursued and documented to ensure that the testing is prudent based on the clinical setting. The impact was measured by the number of orders that have been cancelled or changed. Conclusions: Of 727 bone marrow specimens received, 118 (16.2%) were cancelled subsequently after the clinician was emailed. The most common reasons for cancellation were normal bone marrow aspirate/biopsy report (67 of 118; 56.8%), wrong test ordered (25 of 118; 21.2%), duplicate orders (12 out of 118; 10.2%), and cytogenetic testing was previously done with normal results (10 out of 118; 8.5%). Cancellation of FISH testing when adequate conventional karyotype was obtained was recently instituted (6 out of 75; 8%). A focused intervention can help prevent overutilization of cytogenetic testing as well as encourage collaborative interactions between the pathologists and the oncologists in ensuring better service to the patients. Unnecessary financial burdens for the patient and time-consuming labor for the geneticist can be preempted. This could serve as a tool to help pathology residents learn effective test utilization strategies.